2009
DOI: 10.1111/j.1467-7652.2009.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

A systems approach to plant bioprocess optimization

Abstract: SummaryA dynamic model for plant cell metabolism was used as a basis for a rational analysis of plant production potential in in vitro cultures. The model was calibrated with data from 3-L bioreactor cultures. A dynamic sensitivity analysis framework was developed to analyse the response curves of secondary metabolite production to metabolic and medium perturbations. Simulation results suggest that a straightforward engineering of cell metabolism or medium composition might only have a limited effect on produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, yields still have to be enhanced to meet economical viability. The key nutrients affecting culture performance have been identified (Cloutier et al, 2008;Lamboursain and Jolicoeur, 2005), and it has been demonstrated that culture management can be improved using an in silico model describing cell behavior (Cloutier et al, 2009). Nevertheless, developments in metabolic engineering allowing to deeply modify a plant cell catalytic capacity may clearly benefit from having a better description of the regulation of the metabolic network.…”
Section: Introductionmentioning
confidence: 99%
“…However, yields still have to be enhanced to meet economical viability. The key nutrients affecting culture performance have been identified (Cloutier et al, 2008;Lamboursain and Jolicoeur, 2005), and it has been demonstrated that culture management can be improved using an in silico model describing cell behavior (Cloutier et al, 2009). Nevertheless, developments in metabolic engineering allowing to deeply modify a plant cell catalytic capacity may clearly benefit from having a better description of the regulation of the metabolic network.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous metabolic modeling study on plant cells (Cloutier et al, 2009), a similar problem of under-determination did not hinder the analysis and predictive capacity of the model. An even larger model for cell signaling (Chen et al, 2009), with hundreds of states and parameters, was shown to be insightful, as long as it is trained against experimental data, as our model is.…”
Section: Parameter Identificationmentioning
confidence: 92%
“…In addition to the metabolic fluxes, dynamic models can reflect intracellular metabolites concentration not only at steady state but also in the transient time [10,11,149]. It consequently makes dynamic models a better candidate in comparison with their constraint-based counterparts for the implementation of monitoring and control strategies in bioprocess management [18,19,85,86,148]. However, the hindering obstacles for all kinetic models to reach genome-scale are limited available data for intracellular concentrations and the complex procedure of selecting kinetic rate laws with identifiable mechanistic parameters.…”
Section: Perspectives and Challenges Aheadmentioning
confidence: 99%
“…However, the extent of progress in the model application to accomplish each of these goals depends on several factors, including the industrial importance and the scientific significance of sought-after results. Based on this premise, metabolic modelling has gained substantial importance to enhance bioprocess optimization [18,19], where the increased efficiency leads to cost reduction in million-dollar order of magnitude, and to develop metabolic therapies [11,14], i.e., to push forward cancer treatment. In a broad classification, metabolic models are divided into four categories based on the capability of the model to distinguish between sub-populations of biomass (unsegregated/segregated) and the extent of recognizing the intracellular biochemical components (unstructured/structured) [17,20], (Figure 1).…”
Section: Introductionmentioning
confidence: 99%